Melhores amigos: as relações entre o vínculo entre tutores e pets, experiência de consumo, satisfação e lealdade em petshops - Toledo, Marcelo Vergílio Paganini de (2023)
This study aims to evaluate and analyze the impact that the relationship between the tutor and his pet (Pet Companion) has on his experience as a customer at the pet shop he frequents. When reviewing this literature, no studies were found that related the concept of Pet Companion with the Customer Experience literature, as well as measurement models developed specifically to measure the consumption experience in pet stores. This thesis innovates by presenting an integration of these theoretical frameworks (Pet Companion and Customer Experience) through a theoretical model that has been tested. The translation and adaptation of the scale items, which make up the questionnaire, were done through direct and reverse translations, followed by a survey, for which a Confirmatory Factor Analysis (n=100) was performed. After this validation, another survey was performed, and the results were analyzed using Structural Equation Modeling (n=356). Five hypotheses were tested, of which three were confirmed. The results indicate that, in the researched sample, the consumption experience in a pet shop has a positive impact on customer satisfaction with the same, that customer satisfaction with a pet shop has a positive impact on their loyalty and that the relationship between tutor and its pet (Pet Companion) positively moderates the relationship between consumer experience and customer loyalty. On the other hand, it was also pointed out that the consumption experience in a pet shop does not have a positive impact on the customer's loyalty to the same and that the relationship between the tutor and his pet (Pet Companion) does not positively moderate the relationship between the consumption experience and customer satisfaction. These results provide important theoretical contributions to the field of marketing in relation to pet shops and contributions that cover the continuous improvement of the consumer experience, providing valuable guidelines for the effective management of pet shops, aiming at customer satisfaction and building lasting relationships.